Synthesis of copper-zinc-tin shape memory alloy via electrodeposition of tin on brass - Espiritu, Richard De Villa (2010)
Cu-Zn shape memory alloys were fabricated via electrodeposition of varying amounts of Sn on shin brass substance. The Sn-plated brass strips were then subsequently annealed and rapidly quenched. The resulting ternary alloys were tested for shape memory effect by subjecting the alloy to the flame of a pencil torch and the shape memory response in terms of percent displacement was quantitatively determined. The effects of the following synthesis parameters on the properties of the alloy produced, specifically, grinding profile, type of quenching medium and furnace annealing temperature were determined. Characterization of the Cu_Zn-Sn shape memory alloy in terms of transformation temperatures and energies of transformation were performed using differential scanning calorimetry (DSC), microstructural analysis using optical and scanning electron microscopy (SEM, phase identification and detection of metastable phases by x-ray diffraction analysis (XRD), and compositional analysis carried out by SEM coupled with EDS and x-ray flourescence (XRF) analysis.